CO10 | Multidimensional risk assessment of venous thromboembolism (risk): an observational study comparing the Padua prediction score, Barthel index, and quality of life in hospitalized patients (Bleeding, Thrombosis and Vascular Biology)
Background: Venous thromboembolism (VTE) is a leading cause of preventable morbidity and mortality in hospitalized medical patients. The Padua Prediction Score (PPS) is a validated tool for assessing thrombotic risk in this population, based primarily on clinical and anamnestic factors. However, it does not incorporate parameters of physical autonomy or quality of life, which may significantly influence VTE risk, especially in frail or polymorbid patients. This observational study investigated the interrelationship between PPS, the Barthel Index (BI), and the Health-Related Quality of Life (HRQoL) evaluated using Short Form-36 (SF-36) health survey in hospitalized patients at high risk for VTE, to develop a more comprehensive, multidimensional risk profile.